2021
DOI: 10.1017/dmp.2020.479
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Education Programs for Preparing Children for Natural Hazards: A Systematic Review

Abstract: Schools have a significant role in disaster education to children. This study investigates the research works about school-based education programs in order to discover challenges and best practices. We conducted a systematic review of English language papers published in peer-review journals. The search identified 2577 publications and 61 articles meeting selection criteria and included in the review. Reviewed studies indicated that disaster education in schools is effective but yet insufficient in many co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
8
0
1
Order By: Relevance
“…It has also been suggested that, to help increase knowledge and understanding of disaster risks, the curricular programme can be modified based on each school's local context through its implementation throughout the primary and secondary school years. In fact, school‐based disaster education programmes have been seen as a promising approach for children and youth (Amri et al, 2022; Gokmenoglu et al, 2021; Seddighi et al, 2021) and therefore to community members outside schools.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that, to help increase knowledge and understanding of disaster risks, the curricular programme can be modified based on each school's local context through its implementation throughout the primary and secondary school years. In fact, school‐based disaster education programmes have been seen as a promising approach for children and youth (Amri et al, 2022; Gokmenoglu et al, 2021; Seddighi et al, 2021) and therefore to community members outside schools.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers used a variety of methods to draw students' attention to disasters. According to Seddighi et al (2022), teachers should use various educational equipment for natural disaster preparation, and the curriculum should be revised for better disaster education. All groups that took learner characteristics into account began the class with a drawing attention activity appropriate to the students' level.…”
Section: Discussionmentioning
confidence: 99%
“…The education system is a natural placeto reduce confusing and conflicting information and can play a crucial role in addressing the health and well-being in emergency situations. Schools can provide measured approaches to controversial subject areas, such as the intersection of climate science and natural hazard events and have a significant role to play in children's disaster education [57].The classroom provides a structured environment where follow up support materials, links with other subjects, discussions, and also support can be provided for learners who find natural hazard risk material traumatising.…”
Section: Classroom Deployable Sgmentioning
confidence: 99%